Geotechnical analysis of potential landslides on slopes in the Rimbo Panjang area of Padang City and mitigation - Fardan Fadlan Abileo; Yuliet Rina; Koting Suhana; Mardhiah Ainul; Sucita Ikhsan Bunga; Hafizh; Fadhlurahman Raihan (E3S Web of Conferences)
The Lambung Bukik area of Padang City is a relocation area for the flash flood disaster in Batu Busuk Padang on 24 July 2012. This research analyzes the potential for slope failure in the Rimbo Panjang area, where many residents’ houses are built on steep slopes. Geotechnical analysis was carried out to determine the soil characteristics in the Rimbo Panjang area, which was taken at four locations. The results of the classification show that the soil in the Rimbo Panjang area is inorganic silt - high plasticity (MH). The plasticity index value is 2.5 – 10.4%, indicating that the soil has low swelling potential. The activity value in inorganic silt soil is meager, namely in the range of 0.1 – 0.99, which is the mineral kaolinite and illite activity value. The activity values agree with the XRD test results, where the soil contains kaolinite and illite minerals with low swelling properties. The low swelling characteristic causes the slopes to have a low landslide potential. The safety factor value of the slopes is in the range of 1.79 – 2.71 > 1.5, so the slope can be said to be stable.